Controlled Grazing of Maize Residues Increased Carbon Sequestration in No-Tillage System: A Case of a Smallholder Farm in South Africa - (:unkn) unknown (My University, 2021)
Despite the positive impact of no-tillage (NT) on soil organic carbon (SOC), its potential to reduce soil CO2 emission still needs enhancing for climate change mitigation. Combining NT with controlled-grazing of crop residues is known to increase nutrient cycling; however, the impacts on soil CO2 effluxes require further exploration. This study compared soil CO2 effluxes and SOC stocks from conventional tillage with free grazing (CTFG), NT with free grazing (NTFG), NT without grazing (NTNG), NT without crop residues (NTNR) and NT with controlled-grazing (NTCG), in South Africa. Soil CO2 effluxes were measured 1512 times over two years using LI-COR 6400XT, once to thrice a month. Baseline SOCs data were compared against values obtained at the end of the trial. Overall, NTCG decreased soil CO2 fluxes by 55 and 29% compared to CTFG and NTNR, respectively. NTCG increased SOCs by 3.5-fold compared to NTFG, the other treatments resulted in SOC depletion. The increase in SOCs under NTCG was attributed to high C input and also low soil temperature, which reduce the SOC mineralization rate. Combining NT with postharvest controlled-grazing showed high potential to increase SOCs, which would help to mitigate climate change. However, it was associated with topsoil compaction. Therefore, long-term assessment under different environmental, crop, and soil conditions is still required.
Keywords: African Research